(untitled) (Spectrum, 2022)
This paper explores how Akhtaruzzaman Elias, one of the most influential Bengali writers, rewrites the narrative of the mass uprising of 1969 from the orbit of the subalterns by emphasizing their heroic role as well as the agencies behind their gradual absence from the elitist historiography of nationalism in his novel Chilekothar Sepai [The Soldier in an Attic]. To this end, this paper will refer to the subaltern historian Ranajit Guha’s method of deconstructing historiography of nationalism that looks for an autonomous domain of revolution organized by the subalterns, and Spivak’s postulation of their inability to create a space for themselves within that dominant narrative. Spectrum, Volume 16, June 2021: 53-67